The Heritage of Nusantara Islamic Civilization in West Java (A Study in Sumedang Regency and Cirebon Regency) - Komara, Endang; Mulyanto, Agus; Susilowati, Desi; Setiawan, Fiki; Widiana, Ayu; Nugroho, Iwan Satriyo; Yuswara, Iyus; Herayati (Proceedings: International Seminar On Educational Studies, 2025)
This mini research explores the heritage of Tamadun Islam Nusantara (Nusantara Islamic Civilization) in West Java, focusing on Sumedang and Cirebon as representative cases of agrarian and coastal Islamic civilizations. Using a qualitative descriptive approach combined with systematic literature review and limited field observation, the study reveals that both regions exemplify a harmonious acculturation between universal Islamic teachings and local Sundanese-Javanese wisdom. In Sumedang, the legacy of the Sumedang Larang Kingdom is embodied in the Ngalaksa ritual, leuit (traditional rice barns), and community governance rooted in musyawarah (deliberation), all infused with Islamic monotheism. In Cirebon, the Sultanate’s heritage manifests in the syncretic architecture of the Great Mosque of Sang Cipta Rasa, multicultural religious festivals like Grebeg Maulud, and a governance system integrating adat and Islamic ethics. The research identifies core values of Islam Nusantara—wasathiyyah (moderation), tasamuh (tolerance), rahmatan lil ‘alamin, and hubbul wathan (love for the homeland)—as foundational to both traditions. Despite contextual differences—agrarian sustainability in Sumedang versus intercultural diplomacy in Cirebon—both models affirm that authentic Islam in Indonesia flourished through cultural dialogue, not imposition. This study underscores the relevance of Tamadun Islam Nusantara as a living, dynamic civilization and a strategic ideological resource against religious extremism and cultural erosion.